Mères et fils dans le théâtre de la Renaissance anglaise - Marie-Hélène Besnault (Anglophonia)
Seeking dialogues between mothers and sons as moving and dramatically efficient as the French “Quatre Requêtes de Notre-Dame” results in finding no significant verbal exchanges in English biblical drama, moralities, interludes, and even early tragedies. Mothers are generally reduced to deplorations of sons’ deaths. Shakespeare brilliantly puts an end to this scarcity of dialogues between mothers and sons with plays like Richard III, Coriolanus, and, above all, Hamlet, which this short study eludes. Instead, it focuses on the “‘bard’s” few predecessors and immediate successors, to find continuity, changes, borrowings and new trends concerning reproachful mothers and sons. Among the followers of Noah's sons dealing with their recalcitrant mother, we meet, in Nicholas Udall’s comic interlude Thersites, a son who first teases his mother, then seeks her protection, and ends with reproaches. Shakespeare's immediate successors, Middleton in The Revenger’s Tragedy and Webster in The White Devil, both dramatize relationships between mothers and sons, in several long scenes which we explore, because, unlike Shakespeare’s, they have received little attention.